Perbaikan Kualitas Kimia Vertisol Melalui Pemberian Bahan Organik Mucuna, Crotolaria, dan Dosis Pupuk Hayati - Rupa Matheus; Donatus Kantur (Jurnal Ilmu Pertanian Indonesia, 2022)
The purpose of this study was to evaluate the effect of the treatment of organic material sources Mucuna and Crotolaria and the dose of vesicle arbuscular mycorrhizae (VAM) on the chemical quality of vertisol, nutrient uptake and maize yield in dry land. The research was carried out in the experimental field of the Kupang State Agricultural Polytechnic, in the village of Oesao, East Kupang District, Kupang Regency, East Nusa Tenggara. The study took place from May to September 2021. The study design used a factorial randomized block design. The first factortreatment was source of organic matter (B) of ground cover plant biomass, namely: B0 = no ground cover plant biomass; BM = Mucuna and its biomass are immersed; BC = Crotolaria and its biomass immersed. The second treatment was dose of VAM biofertilizer (D), namely: M0 = 0 g plant-1 (without VAM); M1 = 10 g plant-1; M2 = 20 g plant-1. The results showed that the application of organic material sources and the dose of VAM, respectively, could significantly improve the chemical properties of vertisol. The results showed that the use of organic matter and dose of VAM independently was proven to be the most effective in improving the chemical quality of vertisol. Application of organic matter Mucuna and Crotolaria at a dose of VAM 20 g plant-1 significantly increased N uptake in maize by 53.26‒54.45%, maize P uptake by 27.83% and 28.85%, and the yield of dry shelled corn by 146.92% and 146.92% compared to other treatments. Keywords: organic matter, vesicle arbuscular mycorrhizae, soil chemical